“SIKAP, MOTIVASI, DAN MINAT BERWIRAUSAHA MAHASISWA” (Studi Kasus Pada Mahasiswa Universitas Banten Jaya) - Sev Rahmiyanti (LPPM Universitas Banten jaya, 2020)
This research aims to know the Attitudes, Motivations, and Interestsof Student Entrepreneurship (Case Study of Banten Jaya University Students in Serang City). This research is expected to be useful and provide an overview of the extent to which attitudes and motivations foster student interest in running entrepreneurship. This study, researchersused a quantitative method, with 57 respondents. The research method uses simple linear regression analysis method to conduct data analysis. Data collectionusing a questionnaire. Data isprocessedusing SPSS assistance. The results showed that the attitude and motivation significantly influence the interest in entrepreneurship.